2017
DOI: 10.14720/aas.2017.109.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Utility of some floral characters in the assessment of genetic diversity in sesame (Sesamum indicum L.)

Abstract: Sesame collections were evaluated for quantitative floral characters and data obtained were subjected to various statistical analyses. Result showed narrow diversity in most of the quantitative floral characters with moderate variability in length of flower (2.03-3.27 cm), length of style (1.10-1.40 cm), length of capsule (2.33-2.98 cm) and number of seeds per capsule (38.67 -57.67). Correlation study revealed significantly (p < 0.01) positive correlations for length of ovary versus length of flower (r= 0.70) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…Linked characters may allow simultaneous improvement through correlated responses to selection in the segregating progeny (Bello and Olawuyi 2015). This finding is consistent with positively significant correlations of characters obtained in sesame (Azeez et al 2017), pearl millet (Animasaun et al 2017), and groundnut (Olorunmaiye et al 2019). The performance of the 33 accessions of pearl millet evaluated showed that the leaf length is the attribute as a morphological marker to discriminate the accessions (Suppl.…”
Section: Morphological Variation and Diversitysupporting
confidence: 85%
See 1 more Smart Citation
“…Linked characters may allow simultaneous improvement through correlated responses to selection in the segregating progeny (Bello and Olawuyi 2015). This finding is consistent with positively significant correlations of characters obtained in sesame (Azeez et al 2017), pearl millet (Animasaun et al 2017), and groundnut (Olorunmaiye et al 2019). The performance of the 33 accessions of pearl millet evaluated showed that the leaf length is the attribute as a morphological marker to discriminate the accessions (Suppl.…”
Section: Morphological Variation and Diversitysupporting
confidence: 85%
“…The PC-2, which accounted for 43.79% of the total variation, had plant height contributed the most (0.965), while the PC-3 (1.55%) was dominated by the number of leaves (0.993). The higher eigenvalues for vegetative traits such as leaf length and plant height by PC-1 showed their importance and significance in vegetative differentiation among the accessions (Azeez et al 2017). The plot of PC-1 vs. PC-2 divided the 33 accessions into major groups (Fig.…”
Section: Morphological Variation and Diversitymentioning
confidence: 95%
“…In exploring the genetic diversity of the population based on morphometric parameters, petiole length and leaf dimensions are the most effective in delimiting the populations. Positive correlation has been obtained for morphological and agronomic traits in crop plants (Azeez et al 2017;Olorunmaiye et al 2019).…”
Section: Discussionmentioning
confidence: 89%
“…Las diferentes formas de desarrollo del nectario extrafloral (rudimentario, pequeño, mediano y largo) concuerdan con los resultados obtenidos por Mazzani et al (2007), quienes documentaron la mayor variabilidad para el carácter número de flores por axila y desarrollo de nectarios extraflorales. En relación con longitud de la corola, se presentó una media de 2,64 cm, resultados que son afines con los reportados por Azeez et al (2017), quienes caracterizaron genotipos en un rango entre 2,03 -3,27 cm.…”
Section: B Selección De Accesiones Representativasunclassified